New voices over the air: the transformation of the South African Broadcasting Corporation in a changing South Africa - Louw, P. Eric and Milton, Viola (The Hampton Press communication series, 2012)
Introduction: globalization and South Africa's double transformation -- Policymaking: mixing substantive change and rhetoric -- References -- The SABC in context -- The South African game of ethnic ranking, reranking, and patronage -- The Anglo oligarchy and the early SABC -- An Afrikaner oligarchy captures the SABC -- The White oligarchy in crisis and "his master's voice" -- The SABC and the interregnum -- References -- Transforming the SABC -- Mapping out the future: the Matsepe-Casaburri Board -- Problems encountered in transforming the SABC -- A Casaburri team vision: the need for change -- A Casaburri team vision: the problem of trust -- A Casaburri team vision: the new nation -- A Casaburri team vision: Africanization -- A Casaburri team vision: affirmative action -- A Casaburri team vision: the need to be an interventionist board -- Some Casaburri Board failings -- The SABC and the emerging Black elite -- References -- From broederbond to strugglebond: staffing shifts at the SABC -- American roots of affirmative action -- Affirmative action in the South African context -- The SABC's corrective action policy -- The effects of the restaffing exercise -- References -- The shifting symbolic context: from apartheid to rainbow nation to African nationalism -- The National Party: from apartheid to rainbow nation -- The interregnum: the SABC's "Prague Spring" -- A dominant ANC discourse emerges -- References -- The SABC within the context of a mutating broadcast regulatory framework -- The main agendas driving the early IBA -- The IBA formulates its positions -- IBA action: dealing with the SABC and TBVC broadcasters -- IBA action: dealing with M-Net -- IBA action: facilitating new community and private sector voices -- References -- A modernist nation building broadcaster: a refusal of globalization? -- The new globalized environment -- The ANC's nation-building project as a legacy of apartheid -- The Casaburri team as modernist nation builders -- The McKinsey report: challenging modernist nation building at the SABC? -- Echoes of modernity -- References -- Beyond public service broadcasting -- The regulatory framework: 1998-present -- "Profits before people": the SABC's funding model -- Impact on the SABC and its products -- Conclusion -- References -- ANC hegemony and the SABC -- Shifts in ANC policy -- The SABC: a mouthpiece of the ANC? -- What of the future
https://katalog.adlr.link/Record/0-1601572999